Global‐Scale ULF Waves Associated With SSC Accelerate Magnetospheric Ultrarelativistic Electrons. Issue 3 (2nd March 2019) - Hao, Y. X.; Zong, Q.‐G.; Zhou, X.‐Z.; Rankin, R.; Chen, X. R.; Liu, Y.; Fu, S. Y.; Baker, D. N.; Spence, H. E.; Blake, J. B.; Reeves, G. D.; Claudepierre, S. G.
Abstract: We study electron behavior in the outer radiation belts during the 16 July 2017 storm sudden commencement (SSC), in which prompt intensification of ultrarelativistic electron fluxes was observed at around L = 4.8 by Van Allen Probe B immediately after an interplanetary shock. The electron fluxes in multiple energy channels show clear oscillations in the Pc5 frequency range, although the oscillation characteristics are quite different in different energy channels. At energies above ∼1 MeV, the oscillation periods were very close to the electron drift period, which resembles an energy spectrogram evolution expected for an energetic particle injection event and its drift echoes. At lower energies, however, the oscillation periods hardly depended on the energy: They were very close to the ultralow frequency (ULF) wave period derived from electric field measurements (about 250 s according to wavelet analysis). These complex signatures are consistent with the picture of drift resonance between electrons and short‐lived ULF waves with low azimuthal wave numbers. Good agreement between the observations and numerical simulations confirms that shock‐induced global‐scale ULF waves can efficiently accelerate outer belt ultrarelativistic electrons up to 3.4 MeV over a time scale shorter than 1 hr. Key Points: The flux of ultrarelativistic electrons enhanced by an order of magnitude within 1 hr after SSC on 16 July 2017 Drift resonance between 3.4‐MeV electrons and shock‐induced ULF waves is confirmed The behavior of nonresonant particles in response to the shock indicates the scenario of drift resonance with damping ULF waves